Construction For Fluid Flows Of Tangent Spherical Indicatrix By Flows - Korpinar, Talat; Asil, Vedat (Soc Paranaense Matematica, 2020)
In this article, we obtain the characterizations of tangent spherical indicatrix by inextensible flows in space. Moreover, we obtain some performances for curvatures of a tangent spherical indicatrix.
Keywords: Tangent spherical image; Inextensible flows; Curvatures